The Role of Children's Literature in Cultivating Preservice Teachers as Transformative Intellectuals: A Literature Review. (June 2019) - Flores, Tracey T.; Vlach, Saba Khan; Lammert, Catherine
This review of literacy education scholarship examines the ways that children's literature is used as a resource within literacy methods courses in the preparation of preservice teachers (PTs) as transformative intellectuals. The research indicates that the use of children's literature in literacy methods courses has served two distinct purposes: (a) to engage PTs in learning literacy instructional practices and (b) to engage PTs in building sociocultural knowledge and learning transformative (e.g., culturally relevant) pedagogies. This review is framed by Giroux's call for educators to disrupt technocratic approaches to instruction. The findings emphasize the importance of using children's literature with PTs to broaden PTs' understandings of their future student's lives, so they might engage in transformative pedagogies as future K-12 literacy educators.